The Effect of Emotional Demonstration on Maternal Knowledge and Attitudes Regarding Infant and Young Child Feeding in Samarinda, Indonesia - Nunik Purwandini; Satriani Satriani; Nur Abri (Journal of Community Nutrition Intervention, 2026)
Nutritional problems among children under five, particularly stunting, remain a major public health challenge in East Kalimantan, especially in Samarinda. Findings from a preliminary study indicated that one contributing factor is the low level of maternal knowledge and attitudes regarding Infant and Young Child Feeding (IYCF). This study aimed to analyze the effect of IYCF education using the Emotional Demonstration (Emo-Demo) method on the knowledge and attitudes of mothers with children under five in the service area of Mangkupalas Primary Health Center. This study employed a quasi-experimental design with a pretest–posttest control group approach. A total of 34 mothers of children under five were recruited and divided equally into a control group (Booklet PINTAR, n = 17) and an intervention group (Emo-Demo, n = 17). Data on knowledge and attitudes were collected using structured questionnaires. Despite the observed improvements, it is important to note that significant sociodemographic disparities existed at baseline between the two groups, particularly regarding maternal education and household income. Data analysis was conducted using the Wilcoxon test to assess within-group changes and the Mann–Whitney test for between-group comparisons. The results showed a significant improvement in both knowledge and attitudes in the two groups; however, greater changes were observed in the intervention group. Education using the Emo-Demo method significantly increased maternal knowledge (p = 0.000) and attitudes (p = 0.001). Overall, the Emo-Demo method appeared more effective than printed media, although these findings must be interpreted with caution due to the baseline inequalities.